(untitled) (Bangladesh Journal of Animal Science, 2014)
Two hundred forty Hubbard Classic broiler chicks were used in a 35-day trial to study the effects of supplemental choline on deposition of cardiac, hepatic and abdominal fat in broiler. Birds were fed four types of diet: control diet without choline chloride (T0), diet containing 0.1% choline chloride (T1), 0.2% choline chloride (T2) and 0.3% choline chloride. All birds had access to feed and water ad libitum. Results indicated that, trends for deposition of cardiac, hepatic and abdominal fat was decreasing (P<0.01) in a linear fashion both at 4th and 5th weeks as the level of supplemental choline increased linearly. Maximum deposition of cardiac, hepatic and abdominal fat was observed in birds fed the control diet (T0) and the mean values were 24.4, 34.9 and 4.1 at 4th week and 41.6, 47.8 and 6.2 at the 5th week. In contrast, minimum deposition of cardiac, hepatic and abdominal fat was observed in birds fed diet supplemented with 0.3% choline chloride (T3) and the mean values were 14.5, 19.8 and 1.74 at 4th week and 27.2, 27.8 and 2.2 at 5th week. It was concluded that increasing levels of supplemental choline substantially reduced deposition of cardiac, hepatic and abdominal fat in commercial broiler. DOI: http://dx.doi.org/10.3329/bjas.v43i2.20707 Bang. J. Anim. Sci. 2014. 43 (2): 118-122